The value of age IgG and IL6 in estimating time of viral clearance in asymptomatic or mild patients with COVID-19 - Cao, Xi; Xie, Yong-Li; Zhou, Chun-lei; Mu, Hong (Frontiers in Microbiology, 2023)
Abstract Background The aim of this study was to investigate the relationship between Age, immunoglobin G (IgG), immunoglobin M (IgM), procalcitonin (PCT), and interleukin-6 (IL6), and the time to clear viral nucleic acids in asymptomatic and mild coronavirus disease 2019 (COVID-19) patients, as well as evaluated the predictive value of these biochemical indicators. Methods We performed a retrospective analysis on 1570 individuals who were admitted to Tianjin First Central Hospital and diagnosed with asymptomatic or mild cases. Laboratory data were collected, including age, gender, levels of IgG, IgM, PCT and IL6, as well as results of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) nucleic acid test. These data were statistically analyzed using SPSS software, version 24.0. Result The results indicated that among mild patients, Age, IgG, and the time to clear viral nucleic acids were higher than asymptomatic patients (P<0.05). And the time to clear viral nucleic acids was significantly correlated with Age, IgG, IgM, PCT, and IL6 (P<0.05), IgG (r=-0.445, P<0.001) showed moderate correlations. Using logistic regression analysis, we identified older age, high IL6 levels, and low IgG levels were risk factors for nucleic acid clearance exceeding 14 days (P<0.05). When combining these three indicators to predict the probability of nucleic acid clearance exceeding 14 days in the 1,570 patients, the AUROC was found to be 0.727. Conclusion Age, IgG, and IL6 could potentially serve as useful predictors for nucleic acid clearance exceeding 14 days in asymptomatic and mild COVID-19 patients.